Brief Screening Tool for Disordered Eating in Diabetes: Internal consistency and external validity in a contemporary sample of pediatric patients with type 1 diabetes - Markowitz, Jessica T. (American Diabetes Association, 2010)
OBJECTIVE: To update and validate a diabetes-specific screening tool for disordered eating (the Diabetes Eating Problem Survey [DEPS]) in contemporary youth with type 1 diabetes. RESEARCH DESIGN AND METHODS: A total of 112 youth with type 1 diabetes, ages 13–19 years, completed the DEPS. Higher scores on the DEPS indicate more disordered eating behaviors. Youth and their parents also completed additional surveys to examine diabetes-specific family conflict, negative affect related to blood glucose monitoring, youth quality of life, and diabetes burden. Clinicians provided data on height, weight, A1C, and insulin dosing. The DEPS was revised into a shorter, updated measure and validated. RESULTS: The revised 16-item DEPS (DEPS-R) displayed excellent internal consistency (Cronbach's α = 0.86). Construct validity was demonstrated by positive correlations with zBMI (P = 0.01), A1C (P = 0.001), diabetes-specific family conflict (P < 0.005), youth negative affect around blood glucose monitoring (P = 0.001), parental diabetes-specific burden (P = 0.0005), and negative correlations with frequency of blood glucose monitoring (P = 0.03) and quality of life (P ≤ 0.002). External validity was confirmed against clinician report of insulin restriction. CONCLUSIONS: The DEPS-R is a 16-item diabetes-specific self-report measure of disordered eating that can be completed in <10 min. It demonstrated excellent internal consistency, construct validity, and external validity in this contemporary sample of youth with type 1 diabetes. Future studies should focus on using the DEPS-R to identify high-risk populations for prevention of and early intervention for disordered eating behaviors.